Environmental analysis of different packaging waste collection systems for Istanbul - Turkey case study - ÇİFTÇİOĞLU, GÖKÇEN ALEV; YILAN, GÜLŞAH (ELSEVIER, 2016)
Source-separated collection of recyclable packaging wastes has been a huge issue for cities such as Istanbul considering their socially, economically, culturally and environmentally cosmopolite structure. In order to apply an environmentally effective separation and collection, system has to be analyzed with a holistic approach including whole recycled packaging material amounts, source consumptions and related emissions. In this context, the aim of this study is to determine the environmentally optimum source-separated packaging waste collection system applicable in Istanbul, Turkey for the first time in literature. Eight scenarios for separated collection system were defined and all of them were compared with each other and with the existing system. To measure the efficiency of the system, some efficiency indicators were chosen and effectiveness related variables were determined to predict the participation rate. Calculations of the efficiency indicators for alternative scenarios were based on the existing system. The environmental analysis was conducted by using Life Cycle Assessment methodology. The results of this study showed that existing system was still one of the environmentally most promising scenarios. Following advantageous scenarios were Scenarios 5 and 6 which were two and three fractionated curbside collection systems, respectively. It is also seen that more fractionated scenarios were less beneficial than two fractionated scenarios. And finally, it can be concluded that with an increment on participation rate and changing collection material type, collection efficiency of curbside system would increase and be environmentally more beneficial. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Municipal solid waste; Packaging waste; Source separation; Environmental analysis; Life Cycle Assessment (LCA); LIFE-CYCLE ASSESSMENT; SORTED HOUSEHOLD WASTE; SOLID-WASTE; MANAGEMENT-SYSTEMS; SEPARATED COLLECTION; LCA; PARTICIPATION; SCENARIOS; RECOVERY; MSW